(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
On the basis of the soybean plant, the technology of protein extraction was developed, and according to the results of the analysis, the nitrogen content of sample 1 was 0.43%, and the content of sample 2 was 0.224%. In general protein quantification, however, sample 1 was shown to be 2.71% and sample 2 was shown to be 1.4%. It can be summed up that the presence of irreplaceable amino acids in the grain of a soy plant belonging to the legume family, which has its place on a global scale, determines its nutritional value. Investigations have found that these proteins can be substituted for soy plant proteins in terms of composition reflected in experiments